Development Of Non-Formal Primary School Education Tutor In Facing The Era Of Industrial Revolution 4.0 In Sukabumi City - Nurasiah, Iis; Lyesmaya, Dyah; Ananta, Aidah; Sumiarsa, Deden; Ashlan, Dian (International Journal of Community Service Learning, 2018)
The rapid movement of information technology becoming one of many factors for developing education. This factor is more important today because nowdays we are increasingly unable to separate our lives from information technology.  education is one of the elements affected by the rapid growth of information technology. like it or not we have to balance and adapt to this growth. The Center for Community Learning Activities (PKBM) is an alternative choice for getting an education outside of formal education. In Sukabumi the existence of PKBM needs to be developed and modernized because it has not been touched by professionals. PGSD's dedication team answered this challenge by providing assistance and training at two PKBMs in the city of Sukabumi.  the methodology carried out includes five stages, namely, group selection, socialization, training, reflection, and monitoring and evaluation. The program result is Collaboration between PKBM managers and PGSD Study Programs UMMI helped develop Non-Formal Elementary School Education programs in Sukabumi City